Effect of Old Roasting and Long Immersion on the Quality of Brown Rice Flour (Oryza nivara) - Ujwalita Kumara Amaranggana; Al Machfudz; Ida Agustini Saidi; Rahmah Utami Budiandari (Universitas Muhammadiyah Sidoarjo, 2022)
This study aims to find out the influence of long immersion and long roasting on the quality of brown rice flour. This research was conducted at the Laboratory of Product Development and Food Analysis of the Food Technology Program of the Faculty of Science and Technology, University of Muhammadiyah Sidoarjo from September to November 2021 using a random design of factorial groups. The first factor is the length of immersion consisting of three levels, namely 1 hour, 2 hours, 3 hours, while the second factor is the roasting length of 20 minutes and 30 minutes. Statistical analysis using ANOVA and further tests using BNJ test 5%. Then for organoleptic tests analyzed using the Friedman test. The results showed there was an interaction between the length of immersion and the length of roasting of water content, coarse fiber content, and fat content but did not affect ash content. The best treatment is brown rice flour with a long treatment of 1 hour immersion and a 40-minute roasting length (T1S3) which shows ash levels of 1.32%, water content of 10.36%, fiber content of 20.52%, fat content of 1.65%, organoleptic test aroma 2.88 (somewhat typical of brown rice), organoleptic test color 2.10 (bright red), organoleptic test texture 3.50 (smooth).